Factors influencing ankle alignment changes following medial unicompartmental knee arthroplasty: Preoperative knee and ankle deformities and extent of knee alignment correction - Han-Ting Shih; Shun-Ping Wang; Cheng-Hung Lee; Kao-Chang Tu; Shih-Chieh Tang; Kun-Hui Chen (PLoS ONE, 2025)
Introduction The impact of medial unicompartmental knee arthroplasty (MUKA) on ankle alignment is not well-studied. This study aims to investigate the changes in ankle alignment following MUKA and identify the influencing factors. Materials and Methods A retrospective analysis included 175 patients undergoing MUKA between 2018 and 2020. Patients were categorized into varus (n =  113) or valgus (n =  62) ankle groups based on preoperative ankle deformities. Preoperative and postoperative full-length standing radiographs were used for radiographic measurements. Results Following MUKA, significant differences in the change in tibial plafond-talus angle (PTA) were observed between the groups, with the varus ankle group showing a change of -0.71 ±  0.82° and the valgus ankle group showing a change of 0.08 ±  0.94° (p <  0.001). In the varus ankle group, the tibial plafond-ground angle (PGA) increased from -3.65 ±  4.22° preoperatively to -0.51 ±  4.52° postoperatively (p <  0.001), talus-ground angle (TGA) increased from -5.28 ±  4.32° to -1.32 ±  4.74° (p <  0.001), and PTA decreased from 1.52 ±  1.04° to 0.81 ±  1.12° (p <  0.001). In the valgus ankle group, PGA increased from -5.44 ±  4.39° to -1.43 ±  4.63° (p <  0.001) and TGA increased from -4.55 ±  4.24° to -0.59 ±  4.47° (p <  0.001), but PTA did not show a significant change. Ankle alignment change significantly correlated with preoperative joint line convergence angle (JLCA), preoperative medial proximal tibial angle (MPTA), preoperative PGA, preoperative TGA, preoperative PTA, hip-knee-ankle angle (HKA) changes, and bearing thickness. Conclusions MUKA significantly corrects the majority of ankle alignment towards a more neutral position. The extent of ankle alignment correction is influenced by preoperative knee and ankle joint deformities, as well as the degree of knee alignment correction.